3D printing composite positive pole piece, preparation method thereof and solid-state battery
Through 3D printing of composite positive electrode sheets and in-situ polymerization, the problem of increasing electrode thickness in traditional lithium-ion batteries is solved, the rate performance and cycle stability of solid-state batteries are improved, and efficient lithium-ion transmission and electrochemical performance improvement is achieved. .
Patent Information
- Application Number
- CN202411703251.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-01-10
AI Technical Summary
During the preparation of traditional lithium-ion batteries, high energy density demand leads to an increase in electrode thickness, resulting in difficulty in controlling drying temperature, cracking and extended lithium ion transmission path, affecting electrochemical performance; the content of active substances in 3D printing technology decreases, and the electrochemical performance is improved Limited; solid-state batteries have large interface impedance and poor capacity performance.
3D printing composite positive electrode sheets, containing active substances such as lithium iron phosphate and lithium cobalt oxide, conductive agents, binders, plasticizers and polymer monomers, and are printed on aluminum foil through 3D printing technology and dried in vacuum to combine with the original Solid-state batteries are prepared by position polymerization to improve the bonding between the electrode and the solid electrolyte and reduce the interface impedance.
The effective performance of high-load cathode materials is achieved, the rate performance and cycle stability of solid-state batteries are improved, the manufacturing time and cost are reduced, the bonding between the electrode and the solid electrolyte is improved, and the interface transmission efficiency is improved.
Smart Images

Figure CN119297256A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a 3D printed composite positive electrode plate and a preparation method thereof and a solid-state battery, belonging to the field of 3D printing and lithium-ion solid-state batteries. Background Art
[0002] Since entering the industrial society, the main way to obtain energy is the use of fossil fuels. However, due to their limited reserves and the great pollution to the environment, the development of sustainable clean energy has become a hot topic of concern. Lithium-ion batteries, as one of the most promising energy storage systems, have the advantages of high open circuit voltage, high energy density, low self-discharge rate, and long cycle life, and are widely used.
[0003] In the traditional lithium-ion battery preparation process, in order to meet the high energy density requirements of the battery, it is often necessary to prepare high-load electrodes, which makes the electrode have a relatively high thickness. This not only places high demands on temperature control during drying, but also cannot ensure that the electrode is completely dry at low temperatures, and higher temperatures will cause the electrode to crack. In addition, the increase in thickness leads to an increase in the tortuosity of lithium ion transmission, and a longer lithium ion transmission path, which is not conducive to the full play of electrochemical performance.
[0004] 3D printing technology can achieve changes in electrode structure, which is beneficial to shorten the ion transmission distance and effectively improve the capacity and rate performance of positive electrode materials. However, in order to achieve complete molding and printing of the electrode structure, a large amount of binder content needs to be added to the slurry, which reduces the content of active substances in the electrode, which is not conducive to the improvement of electrochemical performance; in addition, compared with liquid batteries, solid-state batteries are less prone to fire or explosion, but solid-state batteries usually have a larger interface impedance, which is not conducive to capacity development.
[0005] Chinese patent CN114792804A discloses a 3D printed positive electrode ink and a positive electrode forming method and application thereof. The patent mixes the positive electrode active material, solvent and binder and prints them on the current collector aluminum foil. The binder ratio is 10%, and the active material content is also reduced. The active material content is about 70%. Although a complete electrode can be printed, it is not conducive to improving the energy density of the battery; and when applied to liquid batteries, the safety performance is poor. Summary of the invention
[0006] In order to overcome the defects of the prior art, the present invention provides a 3D printed composite positive electrode sheet and a preparation method thereof and a solid-state battery. The technical solution of the present invention is:
[0007] A 3D printed composite positive electrode sheet, comprising a positive electrode active material, a conductive agent, a binder, a plasticizer and a polymer monomer, wherein the mass percentage of the active material is 90-97wt%; the mass percentage of the conductive agent is 1-3.5wt%; the mass percentage of the plasticizer is 0-1.5wt%; the mass percentage of the binder is 1-5wt%; and the mass percentage of the polymer monomer is 1-5wt%.
[0008] The active material is one or a mixture of any proportion of lithium iron phosphate positive electrode material, lithium cobalt oxide positive electrode material, nickel cobalt manganese ternary positive electrode material, and lithium manganese oxide positive electrode material;
[0009] The conductive agent is one or a mixture of any proportion of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes, conductive graphite, and graphene;
[0010] The plasticizer is succinonitrile;
[0011] The binder is one or a mixture of polyvinylidene fluoride, sodium carboxymethyl cellulose and a copolymer of vinylidene fluoride and hexafluoropropylene in any proportion;
[0012] The polymer monomer is one of pentaerythritol triacrylate, 1,3-dioxolane, vinyl ethylene carbonate, polyethylene glycol diacrylate or a mixture thereof in any proportion.
[0013] A method for preparing the 3D printed composite positive electrode sheet comprises the following steps:
[0014] S1. Weigh each component according to the ratio, mix the positive electrode active material, the conductive agent, the binder, the plasticizer and the polymer monomer to form a raw material mixture, and fully stir and mix the raw material mixture in a homogenizer;
[0015] S2, sieving the mixture obtained in step S1 and placing it in a printing barrel, setting the printing parameters of a 3D printer, and using the 3D printer to print electrodes on the aluminum foil current collector;
[0016] S3. The printed electrode is vacuum dried in a vacuum oven to obtain a positive electrode sheet.
[0017] In the step (1), the positive electrode slurry solvent in the homogenizer is N-methylpyrrolidone, and the mass ratio of the positive electrode slurry solvent to the raw material mixture is 17:30.
[0018] In the step S3, the vacuum degree is -0.8 to -1.0 MPa, the drying temperature is 80 to 120° C., and the drying time is 10 to 24 hours.
[0019] A solid-state battery, comprising the 3D printed composite positive electrode plate, wherein the solid-state battery is prepared by in-situ polymerization;
[0020] The solid electrolyte precursor solution for preparing the solid-state battery includes a polymer monomer, an initiator, and an electrolyte and lithium salt mixture, wherein the polymer monomer accounts for 0.01%; the initiator accounts for 0.1%; and the electrolyte and lithium salt mixture accounts for 0.89%.
[0021] The polymer monomer is one or a mixture of pentaerythritol triacrylate, 1,3-dioxolane, vinyl ethylene carbonate, polyethylene glycol diacrylate in any proportion;
[0022] The initiator is one or a mixture of azobisisobutyronitrile, lithium hexafluorophosphate, and aluminum trifluoromethanesulfonate in any proportion;
[0023] The electrolyte is ethylene carbonate or dimethyl carbonate electrolyte containing fluoroethylene carbonate;
[0024] The lithium salt is one of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide or lithium hexafluorophosphate.
[0025] When the in-situ polymerization is carried out, the polymerization temperature is 40 to 80° C. and the polymerization time is 3 to 24 hours. The advantages of the present invention are:
[0026] The raw materials were printed on the positive electrode current collector by 3D printing, and the loading amount of printed active materials was about 7 mg cm -2 In addition, the printed electrode is highly integrated and has a high material utilization rate. Compared with the coating method, it can effectively reduce the battery manufacturing time and cost. The monomer in the electrode polymerizes with the electrolyte precursor solution, which improves the bonding between the solid electrolyte and the electrode, realizes electrode / solid electrolyte integration, and improves the solid-state battery interface, which is beneficial to reduce the interface impedance between the electrolyte and the electrode, accelerate the lithium ion interface transmission, and improve the capacity and rate performance of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a performance chart of rate test of different types of batteries.
[0028] Figure 2 This is a 0.5C cycle performance diagram for different types of batteries.
[0029] Figure 3 This is a 3D printed electrode morphology diagram of the present invention. DETAILED DESCRIPTION
[0030] The present invention will be further described below in conjunction with specific embodiments, and the advantages and features of the present invention will become clearer as the description proceeds. However, these embodiments are exemplary only and do not constitute any limitation to the scope of the present invention. It should be understood by those skilled in the art that the details and forms of the technical solution of the present invention may be modified or replaced without departing from the spirit and scope of the present invention, but these modifications and replacements all fall within the scope of protection of the present invention.
[0031] Embodiment 1: The present invention relates to a 3D printed composite positive electrode plate, wherein a positive electrode active material, a binder, a plasticizer, a conductive agent and a polymer monomer (formula: lithium iron phosphate accounts for 90%, PVDF binder accounts for 4%, conductive agent accounts for 3.5%, plasticizer accounts for 1.5%, PETA polymer monomer accounts for 1%) are mixed and dispersed in a solvent to obtain a slurry; specifically comprising the following steps: S1: Preparation of binder solution: PVDF, SN and PETA are added to NMP (N-methylpyrrolidone), and stirred until the materials are completely dissolved;
[0032] S2: Conductive agent dispersion: Add the conductive agent into S1 and stir thoroughly to disperse it.
[0033] S3: Add active material, add lithium iron phosphate to S2, stir and disperse thoroughly to obtain positive electrode slurry; S4: After filtering the slurry through a 150-mesh sieve, transfer it to a 3D printer for grid printing, with two printing layers, a printing substrate temperature of 60°C, a first layer height of 0.03mm, a printing speed of 10mm / s, and a printing pressure of 0.485Mpa.
[0034] S5: Drying: After the printed electrode is dried in vacuum at a temperature of 110° C., roller pressing is performed at a rolling speed of 5 m / min and a roller gap distance of 20 μm. After rolling, a lithium iron phosphate positive electrode is obtained.
[0035] S6: preparing an in-situ polymerization precursor solution, mixing PETA, azobisisobutyronitrile and the electrolyte and stirring for 30 minutes to obtain a clear, uniform and transparent solution, namely the in-situ polymerization precursor solution.
[0036] The obtained positive electrode sheet, lithium metal negative electrode, PE separator and in-situ polymerization precursor solution are assembled into a CR2032 battery, which specifically includes the following steps:
[0037] S1: Cutting of positive electrode sheets: punching the rolled positive electrode sheets into Φ12mm discs using a manual slicer;
[0038] S2: Preparation of the diaphragm: punch the diaphragm into Φ19 mm discs using a manual slicer and dry them in a vacuum oven at 60°C for 4 h;
[0039] S3: Assemble the battery in the order of positive electrode shell, positive electrode sheet, 40 μL precursor solution, PE diaphragm, 40 μL precursor solution, lithium metal negative electrode, gasket, spring sheet and negative electrode shell, and seal the battery under a pressure of 1000 psi;
[0040] S4: Polymerization of the battery: the battery is placed at 25°C for 10 hours, and then in-situ polymerization is performed. The temperature of the in-situ polymerization is 60°C and the time is 3 hours.
[0041] The assembled polymerized batteries were subjected to rate and long cycle performance tests on the Xinwei equipment. The test cut-off voltage was 2.5-4.0V, the test battery rates were 0.1C, 0.2C, 0.5C, 1C, 2C, 4C, and 0.1C, and the long cycle rate was set to 0.5C. The charge and discharge interval was 2 minutes.
[0042] Example 2
[0043] The positive electrode active material, binder, plasticizer, conductive agent and polymer monomer (formula: lithium iron phosphate accounts for 90%, PVDF binder accounts for 3%, conductive agent accounts for 3.5%, plasticizer accounts for 1.5%, PETA polymer monomer accounts for 2%) are mixed and dispersed in a solvent to obtain a slurry; specifically comprising the following steps:
[0044] S1: Preparation of binder solution: PVDF, SN and PETA are added to NMP (N-methylpyrrolidone) and stirred until the materials are completely dissolved;
[0045] S2: Conductive agent dispersion: add the conductive agent into S1 and stir to disperse it thoroughly;
[0046] S3: Add active material, add lithium iron phosphate to S2, stir and disperse thoroughly to obtain positive electrode slurry;
[0047] S4: After filtering the slurry through a 150-mesh screen, the slurry was transferred to a 3D printer for grid printing. The number of printing layers was two, the printing substrate temperature was 60°C, the first layer height was set to 0.03mm, the printing speed was 10mm / s, and the printing pressure was 0.473Mpa;
[0048] S5: Drying: After the printed electrode is dried in vacuum at a temperature of 110° C., roller pressing is performed at a rolling speed of 5 m / min and a roller gap distance of 20 μm, and a lithium iron phosphate positive electrode is obtained after rolling;
[0049] S6: preparing an in-situ polymerization precursor solution, mixing PETA, azobisisobutyronitrile and the electrolyte and stirring for 30 minutes to obtain a clear, uniform and transparent solution, namely the in-situ polymerization precursor solution.
[0050] The obtained positive electrode sheet, lithium metal negative electrode, PE separator and in-situ polymerization precursor solution are assembled into a CR2032 battery, which specifically includes the following steps:
[0051] S1: Cutting of positive electrode sheets: punching the rolled positive electrode sheets into Φ12mm discs using a manual slicer;
[0052] S2: Preparation of the diaphragm: punch the diaphragm into Φ19 mm discs using a manual slicer and dry them in a vacuum oven at 60°C for 4 h;
[0053] S3: Follow the sequence of positive electrode shell, positive electrode sheet, 40 μL precursor solution, PE diaphragm, 40 μL precursor solution, lithium metal negative electrode, gasket, spring sheet and negative electrode shell.
[0054] Battery assembly and battery sealing at a pressure of 1000psi;
[0055] S4: The battery is placed at 25°C for 10 hours and then polymerized in situ.
[0056] The polymerization temperature was 60°C and the time was 3 h;
[0057] The assembled polymerized batteries were subjected to rate and long cycle performance tests on the Xinwei equipment. The test cut-off voltage was 2.5-4.0V, the test battery rates were 0.1C, 0.2C, 0.5C, 1C, 2C, 4C, and 0.1C, and the long cycle rate was set to 0.5C. The charge and discharge interval was 2 minutes.
[0058] Example 3: The difference from Example 1 is that PVDF accounts for 2wt%, PETA accounts for 3wt%, and the printing pressure is 0.42Mpa.
[0059] Example 4: The difference from Example 1 is that PVDF accounts for 1wt%, PETA accounts for 4wt%, and the printing pressure is set to 0.35Mpa.
[0060] Comparative Example 1: This comparative example is different from Example 1 in that PVDF accounts for 5 wt%, PETA accounts for 0 wt%, and the printing pressure is set to 0.5 MPa.
[0061] Comparative Example 2: The difference between this comparative example and Example 1 is that the comparative example is prepared by coating, and the slurry viscosity is reduced by adjusting the solvent content of the slurry to facilitate coating; wherein, PVDF accounts for 5wt% of the slurry, PETA accounts for 0wt%, the scraper thickness is 200μm, and the coating speed is 15mm / s.
[0062] Table 1 shows the first charge and discharge specific capacities at different rates.
[0063]
[0064] Table 2 shows the capacity retention rate of different types of batteries after 100 cycles at 0.5C.
[0065]
[0066]
[0067] Table 2
[0068] It can be seen from the test data of the above embodiments and comparative examples that the prepared solid-state lithium battery has excellent electrochemical properties; the solid-state lithium battery is tested at a rate of 0.1C-4C, and the step interval of its discharge specific capacity is very small, and the discharge specific capacity is relatively high. Finally, when the rate is set to 0.1C, the battery discharge specific capacity returns to the initial state, indicating that the battery has excellent rate performance; 100 cycles are performed at 0.5C, and the capacity retention rates of Examples 1-4 and Comparative Example 1 are all above 90%. Compared with Comparative Example 2, the capacity retention rate of Comparative Example 2 is 78.15%, indicating that the performance of the solid-state lithium-ion battery prepared by 3D printing electrodes is better than that of coated electrodes.
[0069] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A 3D printed composite positive electrode sheet, characterized in that: It includes positive electrode active material, conductive agent, binder, plasticizer and polymer monomer, wherein the mass percentage of the active material is 90-97wt%; the mass percentage of the conductive agent is 1-3.5wt%; the mass percentage of the plasticizer is 0-1.5wt%; the mass percentage of the binder is 1-5wt%; and the mass percentage of the polymer monomer is 1-5wt%.
2. The 3D printed composite positive electrode sheet according to claim 1, characterized in that: The active material is one or a mixture of any proportion of lithium iron phosphate positive electrode material, lithium cobalt oxide positive electrode material, nickel cobalt manganese ternary positive electrode material, and lithium manganese oxide positive electrode material; The conductive agent is one or a mixture of any proportion of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes, conductive graphite, and graphene; The plasticizer is succinonitrile; The binder is one or a mixture of polyvinylidene fluoride, sodium carboxymethyl cellulose and a copolymer of vinylidene fluoride and hexafluoropropylene in any proportion; The polymer monomer is one of pentaerythritol triacrylate, 1,3-dioxolane, vinyl ethylene carbonate, polyethylene glycol diacrylate or a mixture thereof in any proportion.
3. A method for preparing the 3D printed composite positive electrode sheet according to any one of claims 1 or 2, characterized in that: The steps include: S1. Weigh each component according to the ratio, mix the positive electrode active material, the conductive agent, the binder, the plasticizer and the polymer monomer to form a raw material mixture, and fully stir and mix the raw material mixture in a homogenizer; S2, sieving the mixture obtained in step S1 and placing it in a printing barrel, setting the printing parameters of a 3D printer, and using the 3D printer to print electrodes on the aluminum foil current collector; S3. The printed electrode is vacuum dried in a vacuum oven to obtain a positive electrode sheet.
4. The method according to claim 3, characterized in that: In the step (1), the positive electrode slurry solvent in the homogenizer is N-methylpyrrolidone, and the mass ratio of the positive electrode slurry solvent to the raw material mixture is 17:
30.
5. The method according to claim 3, characterized in that: In the step S3, the vacuum degree is -0.8 to -1.0 MPa, the drying temperature is 80 to 120° C., and the drying time is 10 to 24 hours.
6. A solid-state battery, characterized in that: Including the 3D printed composite positive electrode plate as described in claim 1 or 2, the solid-state battery is prepared by in-situ polymerization;.
7. A solid-state battery according to claim 6, characterized in that: The solid electrolyte precursor solution for preparing the solid-state battery includes a polymer monomer, an initiator, and an electrolyte and lithium salt mixture, wherein the polymer monomer accounts for 0.01%; the initiator accounts for 0.1%; and the electrolyte and lithium salt mixture accounts for 0.89%.
8. The solid-state battery according to claim 7, characterized in that: The polymer monomer is one or a mixture of pentaerythritol triacrylate, 1,3-dioxolane, vinyl ethylene carbonate, polyethylene glycol diacrylate in any proportion; The initiator is one or a mixture of azobisisobutyronitrile, lithium hexafluorophosphate, and aluminum trifluoromethanesulfonate in any proportion; The electrolyte is ethylene carbonate or dimethyl carbonate electrolyte containing fluoroethylene carbonate; The lithium salt is one of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide or lithium hexafluorophosphate.
9. The solid-state battery according to claim 6, characterized in that: When the in-situ polymerization is carried out, the polymerization temperature is 40 to 80° C., and the polymerization time is 3 to 24 hours.
Citation Information
Patent Citations
Positive electrode ink for 3D printing, positive electrode forming method applying positive electrode ink and application
CN114792804A
Method for preparing solid-state lithium ion battery by utilizing 3D printing and obtained lithium ion battery
CN114865096A
Positive pole piece, solid-state battery containing positive pole piece and preparation method of positive pole piece
CN118522979A
Lithium-ion battery in the form of a flexible wire, process for manufacture and uses thereof
WO2019109171A1
Cited By
All-solid-state battery based on 3D printing technology and preparation method
CN120149566A
Preparation method of electrode plate, positive electrode plate, battery cell, solid-state battery and overhang slurry
CN120511270A